AB0832 Increased Serum Uric Acid (SUA) Levels Are A Common Finding in Patients with High Blood Pressure, Insulin Resistance, Obesity and Cardiovascular (CV) Disease. (15th July 2016) - Tasic, I.; Kostic, S.; Skakic, V.; Đorđević, A.; Djordjevic, D.; Radicovic, J.; Nikolic, M.; Andonov, S.; Karadzic, M.; Krstic, I.
Abstract : Objectives: To evaluate the connection between SUA and severity of coronary heart disease (CHD) assessed by angiography in patients with CHD. Methods: 198 patients (75.8% men) undergoing cardiovascular rehabilitation at the Institute "Niska Banja" from October 1, 2014, to January 31, 2015, were evaluated. Mean (SD) patient age (62.1±10.4), prevalence of patients with 3-vessel coronary artery disease with stenosis >70% (31.3%), coronary artery bypass grafting (CABG) (37.4%), percutaneus coronary intervention (PCI) (38.9%), primary PCI (32.8%), mean ejection fraction (50% ±11). Prevalence of hyperuricemia (>386 μmol/l) 33.3%, hypertension 85.9%, hypelipoproteinemia 81.8%, diabetes mellitus 24%, family history of CHD (47%) and mean number risk factors 2.65. Patients were separated into a normal SUA group (n=132, with SUA <386 μmol/L) and a high SUA group (n=66, with SUA ≥386 μmol/L). Results: Patients with high SUA had significantly higher 3-vessel coronary artery disease with stenosis >70% (40.9% vs. 26.5%; P=0.04), low ejection fraction (EF<34%)(19.7% vs. 8.3%; p=0.021), obesity (27% vs. 14.4; P=0.03), significantly higher triglycerides (2.38±1.7 vs. 1.88±1.44; P=0.028) and serum creatinine (111.5±46 vs. 90±21; p<0.001). Conclusions: SUA levels were independently associated with EF in patients with CHD. Hyperuricemia is associated with severity of CAD- 3-vessel coronary artery disease with stenosis >70%. Disclosure of Interest: None declared